1.
а)a²-ab-8a+8b=a(a-b)-8(a-b)=(a-b)(a-8)
б)ab-5b+b²-5a=(ab-5a)+(b²-5b)=a(b-5)+b(b-5)=(b-5)(a+b)
е)7x-xy+7y-x²=(7x+7y)-(x²+xy)=7(x+y)-x(x+y)=(x+y)(7-x)
з)kn-mn-n²+mk=(kn-n²)+(mk-mn)=n(k-n)+m(k-n)=(k-n)(n+m)
2.
а)5a²-5ax-7a+7x =5a(a-x)-7(a-x)=(a-x)(5a-7)
x=-3 a=4
(a-x)(5a-7)=(4-(-3))(20-7)=7·13=91
б)m²-mn-3m+3n=m(m-n)-3(m-n)=(m-n)(m-3)
m=0,5 n=0,25
(m-n)(m-3)=(0,5-0,25)(0,5-3)=0,25·(-2,5)=-0,625
в)a²+ab-11a-11b=a(a+b)-11(a+b)=(a+b)(a-11)
a=6,6 b=0,4
(a+b)(a-11)=(6,6+0,4)·(6,6-11)=7·(-4,4)=-30,8
г)a²-ab-2a+2b=a(a-b)-2(a-b)=(a-b)(a-2)
a=7/20 b=0,15.
(a-b)(a-2)=(7/20 -0,15)·(7/20-2)=(0,35-0,15)(0,35-2)=0,2·(-1,65)=-0,33
Объяснение:
1) m - n + 2p × (m - n)
(m - n) × (1 + 2p)
2) x - xy - 7x + 7y
- 6x - xy + 7y
3) ax + bx + ac + bc
x × (a + b) + c × (a + b)
(a + b) × (x + c)
4) m - mn - 9m + 9n
- 8m - mn + 9n
5) ax - ay + bx - by
a × (x - y) + b × (x - y)
(x + y) × (a + b)
6) px + py - 5x - 5y
p × (x + y) - 5 × (x + y)
(x + y) × (p - 5)
7) 3a - 3c + xa - xc
3 × (a - c) + x × (a - c)
(a - c) × (3 + x)
8) 4a + by + ay + 4b
a × (4 + y) + b × (y + 4)
(4 + y) × (a + b)
9) ab - ac - 4b + 4c
a × (b - c) - 4 × (b - c)
(b - c) × (a - 4)
10) 5a - 5y + pa - py
5 × (a - y) + p × (a - y)
(a - y) × (5 + p)
3/8
Объяснение:
(8/3)⁵ × (3/8)⁶= (8/3)⁵×(8/3)^-6= (8/3)^-1= 3/8